Peningkatan Citra Sekolah SMPIT Bina Anak Sholeh (BIAS) Yogyakarta Melalui Program Special Event - Diningrum Citraningsih; Octarina, Rizqa (STAI Yogyakarta, 2023)
This study aims to describe the management of school image through a special event program at SMP Bina Anak Sholeh Yogyakarta. This type of research belongs to qualitative research. The subjects of this study were principals, teachers, employees, and representatives of students, parents, and local communities. The data collection techniques used are interviews, observation, and documentation. Data analysis techniques are data reduction, data display, and conclusions. Credibility, transferability, dependability, and confirmation tests are applied to test the validity of the data. The results of the study explained that the success of the special event program is supported by good management which includes the process of planning, organizing, implementing, and controlling (evaluation) so as to create public trust and increase public interest in choosing a school for boys / girls at SMPIT BIAS Yogyakarta. The special event program is designed at the beginning of the new school year by involving the committee from the public relations team and several educators and education staff. This activity is carried out twice a year, which is divided into once a semester. The role of school principals and heads of public relations in monitoring activities is one of the indicators of the success of special event programs. In addition, the form of a report after each activity is used for evaluation and follow-up on the next activity program.